Analysis of the Influence of Business Capital, Working Hours and Length of Business on the Income of Grocery Traders in Jambi City - Monica Safitry; Siti Hodijah; Rahma Nurjanah; Bambang Niko Pasla (Badan Pengembangan Sumber Daya Manusia (BPSDM) Provinsi Jambi, 2026)
Introduction/Main Objectives: This study aims to analyze the influence of business capital, working hours, and business duration on the income of grocery traders at Pasar Rakyat Talang Banjar, Jambi City. Research Methods: This research uses a descriptive-analytical quantitative approach. Data were collected through structured interviews with 28 respondents selected using simple random sampling, and analyzed using multiple linear regression with the assistance of SPSS 25 software. Finding/Results: The results show that simultaneously, business capital, working hours, and business duration have a significant effect on income, with a coefficient of determination (R²) of 0.892. Partially, business capital is the most dominant factor, followed by working hours and business duration, all of which have a positive and significant effect on income. Conclusion: In conclusion, increasing traders’ income is strongly influenced by strengthening business capital, optimizing working hours, and accumulating business experience.